89 Referral Patterns, Interventions and Outcomes: A 12 month Retrospective Review of Allied Health Professional Referrals from a Late Effects Clinic. - Grainne Kenny; Rebecca Clark; Agnieszka Kowalska; Philippa MacDonnell; Paula Shukla (Neuro-Oncology, 2026)
Abstract Introduction Access to specialist neurological rehabilitation is recommended at diagnosis of a brain tumour and throughout follow-up to optimise function, treatment tolerance and quality of life. At Guy’s Cancer Centre, Physiotherapy, Occupational Therapy (OT) and Speech and Language Therapy (SLT) are embedded within the neuro-oncology multidisciplinary team. Additionally, a Clinical Nurse Specialist (CNS) led late effects clinic was established to manage long term effects of diagnosis and treatment. This clinic does not have embedded Allied Health Professional (AHP) input; however, patients are increasingly referred to the AHP on-treat neuro-rehabilitation team with identified needs. We reviewed referrals from the late effects clinic to better understand rehabilitation complexity and inform future service development. Method A retrospective review of referrals from the late effects clinic between January and December 2025 was undertaken. Data collected included discipline, referral reason, intervention provided and onward referrals. Results A total of 30 referrals were received: 3 to all disciplines, 18 to both OT and Physiotherapy; 5 to Physiotherapy alone; and 7 to OT. Fatigue was the most common referral reason (n = 18), followed by cognition (n = 11), mobility/ falls (n = 9), sleep difficulties (n = 8), work-related challenges (n = 5), dysphagia (n = 1) and cognitive-communication concerns (n = 1). Of these, 4 patients declined assessment, and 2 were redirected to another service. Among patients seen, 10 received fatigue management support, 9 an exercise programme, and 6 received sleep hygiene intervention. Additionally, 2 patients were supported with concerns regarding work, 2 with cognitive difficulties and 2 given swallow support. Following assessment, 12 patients were referred to community services. Conclusions Patients attending a late effects clinic demonstrate complex rehabilitation needs. Further exploration of how best to provide timely access to appropriate AHP support within survivorship services is warranted.